Exploring the Pharmaceutical Care of Pharmacists in China During COVID-19—A National Multicenter Qualitative Study - Wang, Mingxia; Yin, Zhao; Zhang, Wan; Jia, Xuedong; Du, Shuzhang; Li, Jun; Zhang, Xiaojian (Frontiers in Public Health, 2022)
Background Pharmacists are one of the coronavirus disease-2019 (COVID-19) treatment team members in China, yet only a few single-center studies have described the work experience of pharmacists during the pandemic. Purpose This study aimed to explore in-depth experiences of hospital pharmacists providing pharmacy services during the COVID-19 pandemic in China on a national scale. Methods This is a nationwide multicenter qualitative study that used the purposive sampling method. Semi-structured interviews were conducted with 11 pharmacists from large-scale tertiary hospitals in representative provinces of mainland China. The Colaizzi seven-step method was applied to analyze the interview data. Results Eleven semi-structured interviews were conducted. Each interview lasted 25–70 min. By analyzing the work experiences of pharmacists in COVID-19 designated treatment hospitals, five descriptive themes were categorized: (1) drug supply service; (2) routine clinical pharmacy services; (3) expanded pharmacy services during the epidemic; (4) drug management loopholes; (5) areas of improvements of pharmacy services during a pandemic. Conclusion During the COVID-19 epidemic, Chinese hospital pharmacists played various vital roles. However, there were loopholes in managing narcotic drugs, psychotropic drugs, and donated drugs. The study uncovered areas of improvement in pharmacy services during the pandemic. The emergency response capacity of hospital pharmacists should be continuously improved in the future.